Controllability of stochastic impulsive integro-differential systems involving nonlocal conditions and conformable derivatives - Arthi, Ganesan; Gopika, Suresh Kumar; Nieto, Juan. J. (Nonlinear Analysis: Modelling and Control, 2025)
In this paper, the controllability of a stochastic impulsive integro-differential system involving nonlocal conditions and conformable derivatives is analyzed. The solution of the system is derived by Duhamel’s formula using Laplace and inverse Laplace transforms. The controllability result for the linear system is proved by using controllability Grammian matrix, and for the nonlinear integro-differential system, fixed point techniques are used. The applicability of the system is verified by means of an example.